CD8+ lymphocytes but not B lymphocytes are required for protection against chronic hepatitis E virus infection in chickens. Issue 11 (25th July 2019) - Rogers, Eda; Todd, Stephanie Michelle; Pierson, Frank William; Kenney, Scott P.; Heffron, Connie Lynn; Yugo, Danielle M.; Matzinger, Shannon R.; Mircoff, Elena; Ngo, Irene; Kirby, Charles; Jones, Michaela; Siegel, Paul; et al.
Abstract: Hepatitis E is an important global disease, causing outbreaks of acute hepatitis in many developing countries and sporadic cases in industrialized countries. Hepatitis E virus (HEV) infection typically causes self‐limiting acute hepatitis but can also progress to chronic disease in immunocompromised individuals. The immune response necessary for the prevention of chronic infection is T cell‐dependent; however, the arm of cellular immunity responsible for this protection is not currently known. To investigate the contribution of humoral immunity in control of HEV infection and prevention of chronicity, we experimentally infected 20 wild‐type (WT) and 18 immunoglobulin knockout (JH‐KO) chickens with a chicken strain of HEV (avian HEV). Four weeks postinfection (wpi) with avian HEV, JH‐KO chickens were unable to elicit anti‐HEV antibody but had statistically significantly lower liver lesion scores than the WT chickens. At 16 wpi, viral RNA in fecal material and liver, and severe liver lesions were undetectable in both groups. To determine the role of cytotoxic lymphocytes in the prevention of chronicity, we infected 20 WT and 20 cyclosporine and CD8 + antibody‐treated chickens with the same strain of avian HEV. The CD8 + lymphocyte‐depleted, HEV‐infected chickens had higher incidences of prolonged fecal viral shedding and statistically significantly higher liver lesion scores than the untreated, HEV‐infected birds at 16 wpi. The results indicate that CD8 + lymphocytes are required for viral clearance and reduction of liver lesions in HEV infection while antibodies are not necessary for viral clearance but may contribute to the development of liver lesions in acute HEV infection.